Identification of Key Amino Acid Residues Modulating Intracellular and In vitro Microcin E492 Amyloid Formation - Aguilera, Paulina; Marcoleta, Andrés; Lobos-Ruiz, Pablo; Arranz, Rocío; Valpuesta, José M.; Monasterio, Octavio; Lagos, Rosalba (Frontiers in Microbiology, 2016)
Microcin E492 (MccE492) is a pore-forming bacteriocin produced and exported by Klebsiella pneumoniae RYC492. Besides its antibacterial activity, excreted MccE492 can form amyloid fibrils in vivo as well as in vitro. It has been proposed that bacterial amyloids can be functional playing a biological role, and in the particular case of MccE492 it would control the antibacterial activity. MccE492 amyloid fibril’s morphology and formation kinetics in vitro have been well characterized, however it is not known which amino acid residues determine its amyloidogenic propensity, nor if it forms intracellular amyloid inclusions as has been reported for other bacterial amyloids. In this work we found the conditions in which MccE492 forms intracellular amyloids in E. coli cells, that were visualized as round-shaped inclusion bodies recognized by two amyloidophillic probes, 2-4´-methylaminophenyl benzothiazole and thioflavin-S. We used this property to perform a flow cytometry-based assay to evaluate the aggregation propensity of MccE492 mutants, that were designed using an in silico prediction of putative aggregation hotspots. We established that the predicted amino acid residues 54-63, effectively act as a pro-amyloidogenic stretch. As in the case of other amyloidogenic proteins, this region presented two gatekeeper residues (P57 and P59), which disfavor both intracellular and in vitro MccE492 amyloid formation, preventing an uncontrolled aggregation. Mutants in each of these gatekeeper residues showed faster in vitro aggregation and bactericidal inactivation kinetics, and the two mutants were accumulated as dense amyloid inclusions in more than 80% of E. coli cells expressing these variants. In contrast, the MccE492 mutant lacking residues 54-63 showed a significantly lower intracellular aggregation propensity and slower in vitro polymerization kinetics. Electron microscopy analysis of the amyloids formed in vitro by these mutants revealed that, although with different efficiency, all formed fibrils morphologically similar to wild-type MccE492. The physiological implication of MccE492 intracellular amyloid formation is probably similar to the inactivation process observed for extracellular amyloids, and could be used as a mean of sequestering potentially toxic species inside the cell when this bacteriocin is produced in large amounts.